Analisis Kinerja Layanan Bongkar Muat General Cargo Di Pelabuhan Cappa Ujung Parepare - Arif Fuddin Usman; Andi Ibrahim; Sudarman Sudarman; Muh Azhar Shauqy; Muslihati Muslihati (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
The purpose of this research is to (1) determine the percentage of loading and unloading productivity at the Port of Cappa Ujung Parepare (2) to find out the criteria that have good performance in loading and unloading services at the Port of Cappa Ujung Parepare (3) to find out the criteria that are considered according to the interests of users Loading and unloading services at Cappa Ujung Parepare Port. The population in this study was 120 people, which is the number of respondents in this study related to loading and unloading service assessment performance and the interests of loading and unloading service users. The data collection techniques used were interviews and questionnaires. The data analysis technique in this research was carried out using the Customer Satisfaction Index (CSI) Method and the IPA Analysis Method. The results of this study indicate that (1) The productivity of loading and unloading at the Cappa Ujung Parepare Port in 2021 will reach 5,137,823 Tons/M3 with the biggest achievement in December reaching 1,873% greater than the monthly target. The productivity of loading and unloading at Cappa Ujung Parepare Port in 2022 reached 6,944,242 tons/M3 with the biggest achievement in December reaching 2,510% greater than the monthly target (2) CSI calculation results of 77.64%. Thus, the level of customer satisfaction with loading and unloading services is in the satisfactory category. The highest WF value is shown at 10.42% on attribute 8 (safety in the port environment) which means that this attribute is considered the most important by customers in unloading services. The lowest WF value is shown at 9.69% on attribute 7 (clarity of information about loading and unloading) which means that this attribute is considered not too important by customers in loading and unloading services.